The Practice of Sharia Economics and Capitalist Economics: A Comparative Study - Sofyan Abas (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
A country's economic system actually refers to a unified mechanism and decision-making institutions that implement decisions on economic aspects such as production, consumption, and income distribution. A country's economic system can also be shaped by various complex factors, such as ideology and belief systems, worldviews, geography, politics, socio-culture, and other factors. At the macro level, there are several major schools of thought in the world economy today, including capitalism and Sharia economics. Sharia economics is a superior alternative system because it has a consistent character that does not change over time. Sharia economics is based on the teachings of the Qur'an and Sunnah. The Islamic economy is oriented towards the real sector and is based on profit sharing, unlike the capitalist economic system which is based on usury or interest. The Islamic economy emphasizes not only economic growth but also equity and justice. Meanwhile, the basic concept of the capitalist economic ideology is that fundamental decisions regarding ownership, production, distribution, and consumption can be left to individuals or private parties. The capitalist economic system actually separates religious intervention from various economic and financial activities or transactions. According to Karl Marx, religion is one of the factors that hinders economic growth, monetary stability, and the welfare of society, or an obstacle to economic growth of a nation or country.